Triaxial test and microstructure analysis of soil from alkali contaminated sites - Shaochun Ma; Huimin Xiao; Peng Bao (Case Studies in Construction Materials, 2022)
The protection of site cultural relics is facing great challenges of site soil instability and contamination. Targeting at the special geological environment of Kaifeng region, the affecting laws of different concentrations of alkali on mechanical properties of site soil in this region are studied in this paper. The triaxial test is conducted to study the mechanical properties of site soil, including its failure pattern, stress-strain relationship, stress path and strength index, etc. The X-ray diffraction test and scanning electron microscope test are used to analyze the composition, particle state, and pore characteristics of the soil before and after contamination, and to evaluate the stability of the site soil. At the site combining with microstructure changes and macro mechanical properties. The results show that, from the macroscopic surface, with the increase of alkali concentration, the failure shear plane usually appears along the 45° direction. From the perspective of mechanical properties, the stress-strain relationship of the site soil is caused by the strengthening of soil deformation, and the alkali concentration increases, and the curve gradually develops from hardening type to softening type. The stress path is the line connecting the points in the sequence of the stress change process, which is different, and the corresponding soil deformation and strength characteristics will also appear very different. The stress path of soil with different alkali concentration is different. Under the same σ3 condition, the stress σ1 is different. The stress change is expressed in macroscopic terms as different forms of soil damage. Under 0 % concentration, the strength index of soil is 82.14 kPa, 21.67°, and the alkali concentration is 4–16 %, the internal friction Angle is gradually increased, and the cohesion is slightly reduced. From the micro perspective, the main components of the contaminated site soil are SiO2, Al2O3, CaO and Fe2O3. In the process of alkali-soil reaction, alkali reacts with oxides in soil to form Na2AlO2, which has a certain cementation effect. SiO2 reacts with NaOH solution to generate Na2SiO3, which has strong cohesiveness and strength. The newly generated cementing material in the soil increases, and the bonding force between particles increases. In addition, some cements fill the inner pores and improve the shear strength of soil. Under the same pressure, the stress-strain curve of soil gradually developed from hardening type to softening type with the increase of alkali concentration. In the stress-strain curve of soil, with the increase of alkali concentration, the soil reaches the strength at failure under small deformation. The increase of alkali concentration reduces the plasticity and increases the brittleness of soil. At this time, if the stress is localized, shear bands will appear and the stability of soil will decrease. The study of soil properties changes caused by different alkali pollution concentrations can provide a scientific basis for the reinforcement and protection of soil sites or ancient cultural foundations in Kaifeng area.